(untitled) (Perioperaciina Medicina, 2024)
Introduction: In the past, cholelithiasis in newborns was considered extreme a rare finding, but with increasing use of ultrasound (USG) examination the abdomen is also found more and more often in them. Objective: The objective of the presented work was to assess the frequency of occurrence at least as a guide cholecystolithiasis in newborns and to characterize its spontaneous development or capture it also the occurrence of complications from the biliary system in these children. Materials and Methods: The author examined the cholecyst using USG over four months in 339 newborns (including the period of the COVID-19 pandemic), of which 273 children with adequate postpartum adaptation (“physiological” newborns) and 66 children with postnatal adaptation disorders who required more intensive medical care and in whom they therefore occurred to an increased extent risk factors for the development of cholelithiasis (“pathological” newborns). Results: In 5 children from the first group (1.8 % of these children, of which 3 girls and 2 boys) and in 4 children from the second group (6.1 % of these children, of which 2 girls and 2 boys) was found ultrasound finding of echogenic material in the gallbladder. Among these children, 3 children went (1 from the first and 2 from the second group) o USG image of cholecystolithiasis, in 4 children (3 from the first and 1 from the second group) about the so-called USG image. “sludge-balls” and for 2 children (one from each group) o USG image “sludge”. Frequency of USG image of classic cholecystolithiasis it was thus 0.36 % in “physiological” and 3.0 % in “pathological” newborns. The obvious the predominance of the USG finding of echogenic material in the gallbladder in either gender not recorded by the author. It was found in all “physiological” newborns during subsequent USG checks with the original finding of echogenic material in the gallbladder confirmed spontaneous adjustment USG findings at the age of 1 month. In three of the original 4 “pathological” newborns with the original finding of echogenic material in the gallbladder, this USG persisted image even at the age of three months and at least one of them at the age of over one of the year. They were not observed clinically in any of the monitored newborns significant complications demonstrably related to the biliary system. Conclusion: USG finding of echogenic material in the cholecyst (and also cholecystolithiasis as such) therefore, it can be considered a relatively frequent finding with a good outcome in the newborn age prognosis and the very rare occurrence of complications, while the participation of risky factors in its formation is significant. Despite the good prognosis, USG follow-up should be recommended of these children in order to detect possible complications of cholelithiasis at an early stage.